PROFIL PERUBAHAN AMONIUM, NITRIT DAN NITRAT PADA PERCOBAAN CURAH DARI PDAM BOGOR DAN SURABAYA - Imamuddin, Hartati (Jurnal Teknologi Lingkungan, 2010)
Nitrification is often not effective because the characters of nitrifying bacteria is always slow growing and temperature, pH, DO, amonia concentration, nitrite and C/N ratio as the limited factors. Batch experiment was operated for 6 hours, every half an hours ammonium, nitrite and nitrate were measured.The results showed that added C sourse (glucose) in medium from PDAM Bogorand Surabaya have a significant effects of ammonium degradation, nitrite and nitrate production. Degradation of ammonium in batch reactor from PDAM Bogor showed that both naerobic and aerobic condition have a different fluctuation. Production of nitrite was stable from the middle of reaction to last of aerobic phase. In aerobic condition nitrate production is reduced to 49,21 % (+ glucose) and 60,87% (+ acetate) Batch reactor from PDAM Surabaya differ from PDAM Bogor particularly on degradation of ammonium. Added glucose as C source cause the concentration of ammonium was increased and acetate as C source showed stable with a slightly fluctuation. Nitrite and nitrate production relatively small in both C source.